Making the transition to E-learning : strategies and issues - Bullen, Mark, 1954-; Janes, Diane P., 1960- (Hershey, PA : Information Science Pub., 2007)
'This book provides insights and experiences from e-learning experts from around the world; it address the institutional, pedagogical, and technological issues that higher education institutions are grappling with as they move from conventional face-to-face teaching to e-learning in its diverse forms'--Provided by publisher
Includes bibliographical references and index
Keywords: Education, Higher -- Computer-assisted instruction; Education, Higher -- Effect of technological innovations on